Recovery of calcium from aqueous solutions by fluidized-bed homogeneous granulation process - Tiangco, Kyle Akio A.
Hardness refers to the presence of calcium ions in water due to the dissolution of minerals in the groundwater. While biologically harmless, calcium is an industrial nuisance as it can cause scaling deposits in pipes and reduction in soap and detergent performance. This has led to the use of lime softening as an added step in wastewater treatment plants to control water hardness to regulation standards. While lime softening is an effective treatment option, the production of sludge requires additional resources for drying and disposal. In order to address the problem, fluidized-bed homogeneous crystallization (FBHC) was developed to ensure both high hardness removal rates and production of large, high purity calcium crystals. In this study, FBHC of calcium as calcium carbonate was investigated. A parametric study was conducted to determine the effects of influent calcium concentration, carbonate-to0-calcium molar ratio and carbonate pH on the total calcium removal, granulation efficiency and fines fraction. An optimization study using Response Surface Methodology was also conducted using the same parameters and responses. Modelling and statistical analyses showed the validity of the model and an optimum condition was determined at 300 mg/L Ca2+, [CO3 2-] / [Ca2+] = 1.34, pH 11.00 wherein the granulation efficiency and total calcium removal reached 96% and 98%, respectively. The effect of the presence of fluoride, nitrate and sulfate ions was also tested and each isolated ion showed an increase in granulation efficiency and total calcium removal over the pure calcium solution. Furthermore. the composition and morphological structure of the crystals were analyzed using SEM and XRD with analyses showing the presence of only calcite, which is the most stable form of calcium carbonate. This shows that the treatment of calcium using the FBHC process yields a highly reusable product.